2012
DOI: 10.1111/1574-6941.12009
|View full text |Cite
|
Sign up to set email alerts
|

Chronic N-amended soils exhibit an altered bacterial community structure in Harvard Forest, MA, USA

Abstract: At the Harvard Forest, Petersham, MA, the impact of 20 years of annual ammonium nitrate application to the mixed hardwood stand on soil bacterial communities was studied using 16S rRNA genes pyrosequencing. Amplification of 16S rRNA genes was done using DNA extracted from 30 soil samples (three treatments × two horizons × five subplots) collected from untreated (control), low N-amended (50 kg ha(-1) year(-1)) and high N-amended (150 kg ha(-1) year(-1)) plots. A total of 1.3 million sequences were processed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 87 publications
(117 reference statements)
3
48
1
1
Order By: Relevance
“…Microbial-community composition is often sensitive to the addition of nitrogen 52, 53 . Fierer et al .…”
Section: Discussionmentioning
confidence: 99%
“…Microbial-community composition is often sensitive to the addition of nitrogen 52, 53 . Fierer et al .…”
Section: Discussionmentioning
confidence: 99%
“…Gelsomino et al (2006) reported that the increase of total N observed in soils flooded with wastewater was concomitant with a decrease in the genetic diversity of ammonia-oxidizing bacteria when compared to controls. However, the addition of ammonium nitrate to soils was shown to in-crease the bacterial richness (Turlapati et al, 2013). Friedel et al (2000) studying a soil irrigated with wastewater for more than 18 years demonstrated that denitrifying activity was stimulated comparing to those under rainfed agriculture.…”
Section: Nitrogen Phosphorus and Other Plant Nutrientsmentioning
confidence: 99%
“…Changes in the aboveground tree productivity of both stands was accompanied by changes in the belowground (i.e., soil) fungal and microbial biomass at the HF site (Frey et al, 2004; Wallenstein et al, 2006). In both soil horizons (organic and mineral) at the N-amended hardwood stand, significant rearrangements in bacterial community structure were observed after 20 years of annual N treatment (Turlapati et al, 2013). Biochemical analysis of foliage revealed that Put concentrations were reflective of N storage in most species, and in some, the increase was additive from the response to Ca ++ deficiency caused by soil nutrient leaching.…”
Section: Polyamines As Metabolic Markers Of Long-term Environmental Smentioning
confidence: 99%